Relação entre proteínas de choque térmico, reprodução materna e desenvolvimento fetal em diferentes modelos de diabete - Saito, Felipe Hiroshi [UNESP] (2012)
Embryo implantation and formation of a functional placenta are essential steps for the establishment of pregnancy, survival and development of the embryo and the fetus in the intrauterine environment. Among the various factors involved in embryo-fetal development, heat shock proteins (hsp) play a central role. These proteins function as molecular chaperones and have a highly conserved amino acid sequence, being essential for survival of all organisms from bacteria to plants and mammals. The hsp are essential for cellular survival, thus it is understandable that hsp have gained considerable interest in almost every medical field including reproduction, immunology and infectious diseases. Recent studies have reported the involvement of hsp in various stages of embryonic and fetal development, from formation of the male and female gametes until parturition. Further studies are needed to elucidate the mechanisms by which hsp influence reproductive processes. The purpose of this review is to present and discuss the involvement of hsp on embryonic and fetal development